Tradisionalit Muslims and Modernist Muslim in Indonesia: Past and Present - Faisal Ismail (Al-Jami'ah: Journal of Islamic Studies, 1993)
Indonesia in the early twentieth century witnessed the emergence of an Islamic reform movement, particularly in java and west Sumatra. Historically, this Islamic reform movement led to the division of Indonesian Muslim into two groups, namely Modernist Muslim and Traditionalist Muslim in the country. As a consequence, since this time, Islamic modernism and traditionalism appeared on the stage of Indonesian history and these terms have been used by sociologists, historians, religious scholar, both in Indonesia and abroad. Before continuing to discuss Islamic modernism an Islamic traditionalist, the first thing to know is that both modernist and traditionalist Muslim in Indonesia are Sunni Muslims or ahl-al Sunna wa al-jamā’a, i.e., followers of the Sunna (prophetic traditional) and constitute the majority of the Muslim community (jamā’a). In Indonesia, both Modernist and traditionalist Muslims believe in six pillars of the Islamic faith, i.e., belief in one God, in His predestination. Both groups also observe the five pillars of Islamic practices: shahada (the profession of faith, i.e., there is no god but God, and Muhammad is the messenger of God); payer (five time per day); zakat (almsgiving); fasting during the month of Ramadan; and the hajj or pilgrimage to the holy city of mecca for those who are physically and financially able to perform it.